Career Picture of Students of Special Needs Education in the Spontaneous Process of Music-Making (Training and Practice : Journal of Educational Sciences, 2013)
Non-verbal persons or those with speech difficulties, persons with intellectual, vision, hearing or motor impairments or those showing autistic symptoms, as well as persons with multiple disabilities all have a demand, a right and an ability to communicate. (Erdélyi 2008) The know-how of a special needs teacher involves the ability to establish a connection with these people and to understand them. This is supported by communication through art, including music. What musical ability and affinity do students of special needs education have and how can either be measured? What is their image of teachers and music teachers and how does it influence them in assessment? How can their image of teaching music be changed in the music element of special needs teacher training? Does spontaneous music-making alter their previous assessment abilities and images of teachers? Do students with better musical training exert a greater influence on the group’s music improvisation? How does ability and experience relate to one another in the course of the music-making and which turns out to be more substantial?